Two-Stage Optimal Scheduling of Regional Integrated Energy System Considering V2 G Response of Electric Buses - Zichun YU; Hong FAN; Shiwei XIA (Zhongguo dianli)
Aiming at the problems of wind and photovoltaic power curtailment and total electrical load fluctuation caused by high permeability renewable energy and electric buses access to the system, a two-stage optimal scheduling method of regional integrated energy system considering the vehicle-to-grid (V2G) response of electric buses was proposed. Firstly, under the condition of satisfying the operation plan of electric buses, the V2G response of electric bus cluster is embedded into the optimal scheduling of regional integrated energy system, and the first-stage scheduling strategy is formed with the goal of minimizing the operation cost of the whole system. Then, based on the optimization results of the first stage, the second-stage scheduling model further optimizes the scheduling plan of each equipment and energy interaction strategies with the goal of minimizing the fluctuation rate of total electrical load generated by all electrical equipment in the system. Finally, the results of coordinated scheduling of electric bus cluster and energy equipment in four scenarios are compared and analyzed, the simulation shows that the proposed model can improve the capacity of wind and photovoltaic power accommodation and operation economy of the regional integrated energy system, and reduce the fluctuation of the total electrical load of the system, which verifies the effectiveness of the proposed scheduling method.